2021
DOI: 10.1038/s41408-021-00498-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease assessment by multiparameter flow cytometry in transplant-eligible myeloma in the EMN02/HOVON 95 MM trial

Abstract: Minimal residual disease (MRD) by multiparameter flow cytometry (MFC) is the most effective tool to define a deep response in multiple myeloma (MM). We conducted an MRD correlative study of the EMN02/HO95 MM phase III trial in newly diagnosed MM patients achieving a suspected complete response before maintenance and every 6 months during maintenance. Patients received high-dose melphalan (HDM) versus bortezomib-melphalan-prednisone (VMP) intensification, followed by bortezomib-lenalidomide-dexamethasone (VRd) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…After a median follow-up of 74.8 months, consolidation was associated with a significantly prolonged PFS (median 59.3 months vs. 42.9 months, HR = 0.81, p = 0.016) with OS not reached in both arms despite OS curve separation after 5–6 years in favor of consolidation [ 62 ]. Remarkably, in patients with MRD negativity after consolidation, median PFS was 87 months vs. 38 months in MRD positive (HR = 0.39, p < 0.001), whereas 5-year OS was 82% vs. 69%, respectively (HR = 0.51, p = 0.01) [ 63 ]. On the other hand, the phase III BMT CTN00702 STaMINA trial failed to demonstrate a benefit of consolidation therapy [ 64 ].…”
Section: Where We Are With Consolidation Therapy Post-asctmentioning
confidence: 99%
“…After a median follow-up of 74.8 months, consolidation was associated with a significantly prolonged PFS (median 59.3 months vs. 42.9 months, HR = 0.81, p = 0.016) with OS not reached in both arms despite OS curve separation after 5–6 years in favor of consolidation [ 62 ]. Remarkably, in patients with MRD negativity after consolidation, median PFS was 87 months vs. 38 months in MRD positive (HR = 0.39, p < 0.001), whereas 5-year OS was 82% vs. 69%, respectively (HR = 0.51, p = 0.01) [ 63 ]. On the other hand, the phase III BMT CTN00702 STaMINA trial failed to demonstrate a benefit of consolidation therapy [ 64 ].…”
Section: Where We Are With Consolidation Therapy Post-asctmentioning
confidence: 99%
“…The high and independent prediction accuracy of EuroFlow-NGF, for both OS and PFS, was recently demonstrated in a Spanish prospective study including more than 400 newly diagnosed MM patients; in this large cohort, only 7% of patients without a detectable disease (reported sensitivity of 10 −6 ) relapsed, predominantly with extramedullary disease [ 127 ]. Consistently, in the EMN02/HOVON 95 MM trial, patients with sustained MFC-MRD negativity (sensitivity of 10 −4 –10 −5 ) had a 5-year PFS and OS of 81% and 94%, respectively, thus suggesting that MRD negativity can be used as a surrogate endpoint for survival outcomes [ 128 ].…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 87%
“…A growing number of opinions are claiming the recognition of MRD negativity as a primary end-point for efficacy in clinical trials (65)(66)(67)(68). Additionally, many studies have confirmed the prognostic power of MRD kinetics based on the evidences obtained during the maintenance phase of treatment at the frontline (69)(70)(71).…”
Section: The Settlement Of Measurable Residual Disease In Clinical Pr...mentioning
confidence: 99%